Students’ Mental Models of Acid and Base Concepts Taught Using Cognitive Apprenticeship Learning Model - Amalia, F. R.; Ibnu, S.; Widarti, H. R.; Wuni, H. (Jurnal Pendidikan IPA Indonesia, 2018)
A mental model is a student's perception or description of a concept. Chemistry learning requires deep understanding including three levels of representation; macroscopic, sub-microscopic, and symbolic. These three levels of representation are interconnected to form a meaningful understanding and students' mental model. The purpose of this study was to look at the mental models of students on acid and base topic taught using cognitive apprenticeship learning model. This research employed explanatory sequential mix method with 65 research subjects. The research instrument was in the form of a description test of acid-base concepts and an interview guideline for the students’ answers on the test. The results showed that students had good mental models (63.64%) on acid and base taught using cognitive apprenticeship learning model.